Instruction-Tuned Qwen2.5 Models vs. Prior Iterations on Multi-Turn Dialogue Benchmarks - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 15 peer-reviewed papers addressing the following research question: What is the comparative performance of instruction-tuned Qwen2.5 models versus previous iterations on multi-turn dialogue benchmarks like MT-Bench regarding helpfulness and safety alignment. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 5.5/10. This report is a mach
Machine-generated literature synthesis.